Сonceptual and terminological apparatus of research on strategies of higher education institutions positioning in the international information space - Hyrka, I. (Problems of Engineer-Pedagogical Education, 2020)
The article is devoted to a detailed analysis of the essence of the concepts of “franchising”, “franchise”, “benchmarking”, “university”, “leading university”, “educational service”, “educational product”, “educational marketing”, “higher education institution positioning strategy”, “fundraising” , “rating”, “PR-activity”, “background”, “information space”, “international information space” and discloses their contents. A theoretical analysis of scientific works devoted to the strategy of positioning leading universities in the international information space confirms that the development and prestige of an educational institution is very important in the modern information society not only in Ukraine, but also abroad. Therefore, it is crucial to have a stable position among competitors in the education market in order to provide oneself with creative students who aspire to study and want to get a quality education as well as with qualified employees who ensure a continuous process of studying disciplines using the modern information space, and prestigious work that could bring not only a decent salary, but also a sense of satisfaction. The author defines the subject areas for using information on successful achievements of higher education institutions, which include current applicants and future higher education applicants who want to get more information about higher education institutions to meet their own needs; scientists who pay attention to the future for their own purposes (career growth), teachers who seek to improve the level and quality of students' knowledge in teaching to enhance the educational process; parents of future students who want to know the level of prestige and quality of education in the higher learning institution for further successful employment; university administration seeking to demonstrate achievements to parents and the head of the institutions as well as to provide reasons explaining the need to allocate additional resources; representatives of the media willing to disseminate useful data for society and employers who look for information about the level of knowledge and competence of graduates of higher educational institutions.